Impacts of RCEP’s trade barrier reductions on China’s agricultural trade: A GTAP simulation - Hangqi Cai; Zefang Liao; Tianhao Li (PLoS ONE, 2025)
Against the backdrop of a complex and volatile global trade environment, the entry into force of the Regional Comprehensive Economic Partnership (RCEP) has brought new opportunities for regional economic development. From a China-centric perspective, this paper constructs a two-dimensional analytical framework of tariff reduction and non-tariff barriers (NTB) reduction based on theories of regional economic integration and general equilibrium, and uses the GTAP-Dyn model to systematically examine the impact mechanisms and policy effects of RCEP implementation on agricultural trade among member states. The study finds: ①Ten years after RCEP’s implementation, it significantly promotes economic growth in all countries. Taking China as an example, NTB reduction contributes 68.4% to this growth, revealing the dominant role of non-tariff barriers (institutional coordination) in deep regional integration. ②The agricultural sector exhibits a “dual differentiation” feature: sensitive sectors face adjustment pressures (dairy output −21.55%) while domestic substitution effects emerge (aquatic product imports −88.09%). ③Policy effects show national heterogeneity: ASEAN countries experience low growth but high gains (GDP + 0.75%, terms of trade +8.88%), reflecting a complex game landscape. ④The interaction between tariff and non-tariff measures is asymmetric, with long-term dividends relying more on institutional openness. Based on these findings, China should build a composite open system, implement differentiated agricultural policies, and deepen cooperation pathways.